Strategi Content Marketing Pada Media Sosial Tiktok Gebcell - Nisa Alifah Zahra (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The research entitled "CONTENT MARKETING STRATEGY ON TIKTOK GEBCELL SOCIAL MEDIA ACCOUNTS" aims to find out planning, organizing, actuacting, and controlling in content marketing strategies on Gebcell's tiktok social media accounts. The method used is qualitative study using field research and descriptive research types. In this study, the research techniques used were interviews, observations and documentation. The research respondents consisted of 10 students as core informants and 1 academic respondent as expert informants. The results of the study revealed that.